Razvijanje družinske pismenosti: V objemu besed: priročnik za starše (University of Maribor Press, 2017)
Developing Family Literacy Hugged by Words: Parent’s Guide. Monograph Developing Family Literacy Hugged by Words: Manual for Parents is a result of the research project Hugged by Words, financed by the Ministry of Culture of RS (duration October 2016 till November 2017). Its area is encouragement of family reading or family literacy, a part of reading literacy (essential for successful inclusion of people in the society) and includes intergenerrational reading in all areas of kindergarten work (language, art, society, nature, mathematics, movement) and in all areas of child’s development (cognitive, social, emotional, aesthetical, moral-ethical and motivational). Primarily, monograph Hugged by Words was published, on the basis of which a professional manual for parents was prepared. In a simple but proffessional manner the manual for parents contributes to raising awareness of the importance of reading as a lifelong process. We define family literacy as various family activities, linked to literacy in the widest sense, when all family generations cooperate, the result being joint learning. With the factors encouraging reading literacy (IFLA, 2006: being surrounded with reading material, reading to the child, the adult as a reading model) various encouragements are presented for building a positive relationship towards reading culture and habits, linked to literacy.